2012
DOI: 10.1194/jlr.m027185
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic analysis and identification of a role for the orphan human cytochrome P450 2W1 in selective oxidation of lysophospholipids

Abstract: Human cytochrome P450 (P450) 2W1 is still considered an "orphan" because its physiological function is not characterized. To identify its substrate specifi city, the purifi ed recombinant enzyme was incubated with colorectal cancer extracts for untargeted substrate searches using an LC/ MS-based metabolomic and isotopic labeling approach. In addition to previously reported fatty acids, oleyl (18:1) lysophosphatidylcholine (LPC, lysolecithin) was identifi ed as a substrate for P450 2W1. Other human P450 enzymes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…Clinical studies indicate that increased levels of CYP2W1 expression positively correlate with the degree of tumor malignancy, as well as with decreased 10-year survival in patients with colon cancer (12,13). So far, several groups have reported on the metabolism of a few candidate substrates (i.e., benzopyrene, sterigmatocystin, aflatoxin B1, lysophospholipids, and fluorobenzothiazoles) for CYP2W1 expressed in E. coli or mammalian cells (14)(15)(16)(17)(18)(19). However, the potential of CYP2W1 as a specific target in cancer chemotherapy remains hitherto unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies indicate that increased levels of CYP2W1 expression positively correlate with the degree of tumor malignancy, as well as with decreased 10-year survival in patients with colon cancer (12,13). So far, several groups have reported on the metabolism of a few candidate substrates (i.e., benzopyrene, sterigmatocystin, aflatoxin B1, lysophospholipids, and fluorobenzothiazoles) for CYP2W1 expressed in E. coli or mammalian cells (14)(15)(16)(17)(18)(19). However, the potential of CYP2W1 as a specific target in cancer chemotherapy remains hitherto unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Fatty acids are known to be hydroxylated by P450s at the -carbon and the -1, -2, and -3 positions (3, 51, 52). However, midchain hydroxylations (14) and ␣-and ␤-hydroxylations (53,54) are also known. We found that P450 2U1 yielded a reverse type I difference spectrum (46), generally considered to indicate a change in the iron spin state (from high to low spin), because of an increase in the occupancy of H 2 O as the distal ligand.…”
Section: Discussionmentioning
confidence: 99%
“…Other metabolomics data mining software was also used, e.g. MZmine (39) and an in-house Matlab program (14) for doublet searches (M, M ϩ 2) in the case of 18 O-based isotopic labeling experiments. MZmine2 (40) serves as a high performance tool in differential analysis of data from multiple LC-MS experiments, enabling noise filtering, peak detection, and retention time (t R ) alignment for corresponding peaks from different runs (40).…”
Section: Lc-ms Metabolomicmentioning
confidence: 99%
See 2 more Smart Citations